The effects of inhalation of oxygen and carbon dioxide mixtures on noise-induced temporary threshold shift in humans - Patchett, R.F. (Canadian Acoustics, 1992)
Sixteen subjects breathed either oxygen, carbogen, air with 5% carbon dioxide or air while subjected to 10 min of 100 dB noise and for a further 10 min in order to explore the effect of the various gases on the establishment and recovery of noise-induced temporary hearing threshold shift. Oxygen and carbogen were found to be effective but not different in effectiveness in reducing the establishment of temporary threshold shift suggesting that the role of carbon dioxide in the process is minimal. No evidence was found to suggest that oxygen or carbogen inhalation assists in recovery from temporary threshold shift